Penggunaan Fotografi Forensik Oleh Penyidik Kepolisian Polresta Surakarta Dalam Penyidikan Tindak Pidana( Studi Kasus Di Polresta Surakarta ) - Isdiyanto, Eko, Hartanto, S.H., M.Hum, Muchamad Iksan, S.H., M.H (2016)
Investigations are compulsory and must be done in the search for truth o the occurence of criminal. Intake of evidence as much - many will make it easier for investigators to obtain the truth. The role of police investigators is important, it takes special skills also experience in obtaining eviedence. Forensic photography is a photograph to record objects, scenes, and events for use in a legal process, Forensic photography can be used specifically for documentation, analysis, intelligence, or for presentation in court. The identification process in using photography to the police in order to understand penggunakaanya covers techniques of shooting, shooting identification, various types of portraits, make a copy / reproduction, making photo evidence, shooting at the crime scene, footprints and shoes, soles on objects dusty, former footprint banda, drops of blood, bullets and shell casings, fragments and other small objects related to the case under investigation.